Herpes Zoster Infection Presenting as Aseptic Meningitis and Dermatomal Rash in Immunocompetent Adult - Suyash Dawadi; Sudesh Lamsal; Bhupendra Shah (Case Reports in Infectious Diseases)
Herpes zoster is a localized, painful, and vesicular rash involving one or adjacent dermatomes caused by varicella-zoster virus reactivation. Herpes zoster presenting as aseptic meningitis is prevalent among elderly population and people with immunocompromised status. However, it is a rare phenomenon in the young immunocompetent adult; hence, we are reporting a case of a herpes zoster infection presenting as aseptic meningitis and dermatological manifestation in a 19-year-old immunocompetent male.